Antifungal potentiality of the latex of Plumeria acutifolia Poir - and A.K. DAS, SASWATI SENGUPTA*, S.N. GHOSH (Indian Phytopathology, 2008)
Latex of Plumeria acutifolia Poir showed antifungal properties against Acremonium kiliense, Myrothecium roridum, Penicillium expansum and Rhizoctonia solani. The MIC values of Plumeria acutifolia are 100-200mg/ml against the tested microorganisms, which are satisfactory. The TLC study revealed that the plant extract contained fractions of alkaloids and glycoside, which also have more or less antifungal activities. The seed treatment by this plant extract showed more effectiveness in reducing disease in rice plants against the damage caused by Rhizoctonia solani, as compared to foliar spray treatment.